Hemothorax After Endobronchial Ultrasound-guided Transbronchial Needle Aspiration. Issue 4 (October 2016) - Franco, José; Llopis, Estefanía; Galán, Genaro
Abstract : Endobronchial ultrasound-guided transbronchial needle aspiration is a minimally invasive method for diagnosing paratracheal and peribronchial lesions, with a low rate of complications. However, as the procedure has gained widespread acceptance, major complications have occasionally been reported. In this report, we describe a case of hemothorax after endobronchial ultrasound-guided transbronchial needle aspiration in a patient with a right upper lobe mass.